Ethical Covert Research - Spicker, Paul (Sociology (Oxford), 2011)
Covert research is research which is not declared to the research participants or subjects. This is often muddled with deception, and condemned as intrinsically unethical. The basis of that condemnation is a legitimate concern with the rights of research subjects. It is, however, overgeneralized. Research subjects do have rights, but they are not the only people with rights. They may have some say about the use of information, but not all information is under their control. They are entitled to privacy, but not everything is private. Undeclared, undisclosed research in informal settings has to be accepted as a normal part of academic enquiry.